Seasonal to decadal spatiotemporal variations of the global ocean carbon sink. (20th December 2021) - Zhang, Min; Cheng, Yangyan; Bao, Ying; Zhao, Chang; Wang, Gang; Zhang, Yuanling; Song, Zhenya; Wu, Zhaohua; Qiao, Fangli
Abstract: The global ocean has absorbed approximately 30% of anthropogenic CO2  since the beginning of the industrial revolution. However, the spatiotemporal evolution of this important global carbon sink varies substantially on all timescales and has not yet been well evaluated. Here, based on a reconstructed observation‐based product of surface ocean pCO2 and air–sea CO2  flux (the MPI‐SOMFFN method), we investigated seasonal to decadal spatiotemporal variations of the ocean CO2  sink during the past three decades using an adaptive data analysis method. Two predominant variations are modulated annual cycles and decadal fluctuations, which account for approximately 46% and 25% of all extracted components, respectively. Although the whole summer to non‐summer seasonal difference pattern is determined by the Southern Ocean, the non‐summer CO2  sink at mid‐latitudes in both hemispheres shows an increasing trend (a total increase of approximately 1.0 PgC during the period 1982–2019), while it is relatively stable in summer. On decadal timescales for the global ocean carbon sink, unlike the weakening decade (1990–1999) and the reinvigoration decade (2000–2009) in which the Southern Ocean plays the dominant role, the reinforcement decade (2010–2019) is mainly the result from the weakening source effect in the equatorial Pacific Ocean. Our results suggest that except for the Southern Ocean's role in the global ocean carbon sink, the strengthening non‐summer's sink at mid‐latitudes in both hemispheres and the decadal or longer timescales of equatorial Pacific Ocean dynamics should be fully considered in understanding the oceanic carbon cycle on a global scale. Abstract : Based on a reconstructed observational‐based product of the surface ocean air–sea CO2  flux (the MPI‐SOMFFN method), we explore the pattern of spatiotemporal variations of the oceanic CO2  sink from seasonal to decadal timescales over the past three decades using an adaptive data analysis method. Two predominant variations are modulated annual cycles (46%) and decadal fluctuations (25%). On decadal timescales, unlike the weakening decade (1990–1999) and the reinvigoration decade (2000–2009) in which the Southern Ocean plays the dominant role, the reinforcement decade (2010–2019) is mainly the result of the weakening source effect in the equatorial Pacific Ocean.